Assessment of the impact of IT outsourcing on IT education in Malaysian institutions of higher learnings - Ahlan, Abdul Rahman; Suhaimi, Mohd Adam; Hussin, Husnayati; Arshad, Yusri (World Scientific and Engineering Academy and Society, 2008)
Malaysia is aggressively promoting its shared services and outsourcing (SSO) business models across vertical industries as a preferred hub in Asia. It is projected for multiple growths in demand for IT graduates to fulfill this IT outsourcing phenomenon by 2012. This poses a question to the Institutions of Higher Learnings (IHLs) in Malaysia. Can the present IT curriculum equip the graduates with skills and knowledge for different vertical industries and produce knowledge workers? In this study, we not only examined and reviewed available literature, newspaper and web articles, companies’ websites and press releases but also sought indepth insights and experiences from senior executive managements in service provider firms in Klang Valley on the skills and capabilities requirements of fresh IT graduates to fulfill the market needs of IT outsourcing in Malaysia. In addition, a CEO roundtable discussion was held in International Islamic University Malaysia which also discussed on the topic. The research team found that technical, soft and problem-solving skills are the main areas of concerns necessary to develop knowledge workers that meet the requirements of the SSO industry